Malay aesthetic principles in the roof decorative architectural components of Rumah Limas Bumbung Perak / Iryani Abdul Halim Choo, Mohd Sabrizaa Abdul Rashid and Nazrul Helmy Jamaludin - Abdul Halim Choo, Iryani; Abdul Rashid, Mohd Sabrizaa; Jamaludin, Nazrul Helmy (Faculty of Art and Design, 2024)
The decorative architectural components of traditional Malay houses are made of beautiful wood carvings that are made up of exquisite motifs, compositions, and carving techniques. These components not only complement the overall aesthetic look of the house but are also rich with symbolism and meaning that reflects the culture and identity of the Malay. Due to this, decorative architectural components are among the components that have been used and integrated into contemporary building design in the spirit of lifting the nation’s identity into modern contemporary design. However, the lack of a comprehensive understanding of the intricate designs and distinctive characteristics of these decorative architectural components has led to a shallow interpretation in contemporary architectural design, ultimately affecting the public's understanding of the traditional Malay architectural heritage. This research aims to analyse the existence of Malay aesthetic principles that exist in decorative architectural components design. The findings of the research found that 6 Malay aesthetic principles exist in the design and placement of the decorative architectural components of Rumah Limas Bumbung Perak, namely, Berhalus (fineness), Berlambang (symbolic), Bermakna (meaningful), Bersatu (unity), Berguna (usefulness), Berlawan (contradict). The findings of this research shed light on the intricate craftsmanship and artistic expression embedded within the decorative architectural components of the traditional Malay house. The significance of the research not only reinforces prior research and extends the understanding of Malay aesthetic principles resonating within the realm of Malay architecture but also it helps the architects and designer to better understand the Malay architecture and its decorative components.